Komposisi dan Struktur Komunitas Ikan Kepe-Kepe (Famili Chaetodontidae) di Perairan Pantai Taman Nirwana, Kota Padang - Suci Frimanozi; Indra Junaidi Zakaria; - Izmiarti (Universitas Andalas, 2014)
A study on the community of butterfly fish (Chaetodontidae) has been conducted from April to June 2013 in two locations of coral reefs at Taman Nirwana coastal area, Padang, namely tourism zone and mangrove zone. This study aimed to determine composition and community structure of butterfly fish. This study used visual census method with limitation of 2.5 meters of view to the left and to the right along the line transects. The results found that nine species of butterfly fish which belong to two genera; Heniochus and Chaetodon. There were three species of Heniochus (i.e Heniochus pleurotaenia, H. varius, and H. Singularis) and six species of Chaetodon (i.e Chaetodon triangulum, C. collare, C. vagabundus, C. trifasciatus, C. rafflesii, and C. Kleinii). The abundance and species diversity of butterfly fish did not significantly differed between tourism and mangrove zones. In line with the two previous parameters, similarity indices were found very close between the tourism and mangrove zones. The low index values for all of the parameters may indicate a low quality of the coastal area community due to the human interferences.Key word : Chaetodontidae, composition, community structure, Nirwana Park beach-Padang